Inhibitory Molecules PD-1, CD73 and CD39 Are Expressed by CD8+ T Cells in a Tissue-Dependent Manner and Can Inhibit T Cell Responses to Stimulation - Smith, Corinne J.; Snyder, Christopher M. (Frontiers in Immunology, 2021)
The salivary gland is an important tissue for persistence and transmission of multiple viruses. Previous work showed that salivary gland tissue-resident CD8+ T cells elicited by viruses were poorly functional ex vivo. Using a model of persistent murine cytomegalovirus (MCMV) infection, we now show that CD8+ T cells in the salivary gland and other non-lymphoid tissues of mice express multiple molecules associated with T cell exhaustion including PD-1, CD73 and CD39. Strikingly however, these molecules were expressed independently of virus or antigen. Rather, PD-1-expressing T cells remained PD-1+ after migration into tissues regardless of infection, while CD73 was activated on CD8+ T cells by TGF- signaling. Blockade of PD-L1, but not CD73, improved cytokine production by salivary gland T cells ex vivo and increased the expression of granzyme B after stimulation within the salivary gland. Nevertheless, salivary-gland localized CD8+ T cells could kill PD-L1-expressing targets in vivo, albeit with modest efficiency, and this was not improved by PD-L1 blockade. Moreover, the impact of PD-L1 blockade on granzyme B expression waned with time. In contrast, the function of kidney-localized T cells was improved by CD73 blockade, but was unaffected by PD-L1 blockade. These data show that tissue localization per se is associated with expression of inhibitory molecules that can impact T cell function, but that the functional impact of this expression is context- and tissue-dependent.